Network Survivability Analysis Modeling Approach for MANETS : A Systematic Review - Azni, AH; Ahmad, R; Noh, ZAM; Hazwani, F; Hayaati, N (IEEE, 2024)
Network survivability analysis modeling in MANETs was hardly an issue in the early years of wireless technology because there was no critical network system that depended on wireless technology yet. Today, network survivability analysis is an essential aspect of reliable communication especially in MANETs. Although various methods have been proposed to model network survivability analysis in MANETs, no related review has been published as to date for this topic. Thus, a comprehensive review of this body of work would be beneficial to researchers to have an overview of the current state of research trend in this area. This paper provides a systematic literature review (SLR) of the state of the art approach in modeling network survivability analysis in MANETs. We used studies from a number of relevant article sources, and our results showed the existence of twenty six articles. From this SLR we found that the existing of modeling method is focusing on individual node in which the node is treated as independent event. Furthermore, the analysis also reveals the less popular methods in modeling network survivability analysis are with statistical methods such as regression analysis and survival analysis. The implication of this study is to give a clear direction to future researchers in this area for a better and accurate analysis in measuring network survivability in MANETs.